KARAKTERISTIK MUTU MINYAK SAWIT MENTAH YANG BERASAL DARI DATARAN TINGGI - Ika Ucha Pradifta Rangkuti (Institut Teknologi Sawit Indonesia, 2017)
Palm oil is a vegetable oil intended for oleofood and oleochemical products. Consumption of products are increasing. This study aims to determine the quality characteristics measured through free fatty acids, peroxide numbers and color of palm oil that produced from higlands crop. Palm fruits used in this study were obtained from Bah Birung Ulu Estate North Sumatera owned by PTPN 4 with an altitude 850 meters above sea level. Palm oil that produced from highland crops have free fatty acids (FFA) that increase with the increase of fruits maturity. FFA at the initial phase of maturity and after maturity phase (over ripa) were 5%, 7.6%, and 8,7 % respectively. Peroxide numbers and color of crude palm oil were ﬂuctuating according to fruit maturity. The red color of crude palm oil at the beginning of fruit maturity will increase as the fruit maturity increases but will decrease over ripe phase.